Reaksjonær radikalisme: Hamsuns vitalistiske poetikk - Boasson, Frode Lerum (Nordlit, 2016)
This article challenges a non-political interpretation of Hamsun’s work, by arguing that Hamsun’s poetics is characterized by a radical reactionary vitalism.